The influence of indigenous languages on Ugandan English as used in the media - Tukwasibwe, Constance (Rhodes University, Faculty of Humanities, School of Languages, 2014)
When two or more languages come in contact, they influence each other in various ways, for example through word borrowing, transfer of sounds, morphology and syntax taken from one language system and imported to another. In this study, the primary concern is on the indigenous communities of Uganda learning the English language, plus the influence that this interaction brings into the linguistic space. Bringing the Ugandan multilingual situation into perspective, the study looks at how the English language has interacted with the local languages and the local speech habits, customs and traditions of the indigenous people, to the extent that it has been indigenized. Some word usage results in miscommunication due to the socio-cultural uniqueness of Ugandan cultural expressions. As an example, because of the practice of polygamy in most Ugandan cultures, words like co-wife are coined to mean 'a woman who shares a husband, or a husband's other wife', a word that is absent in both the language and culture of native English speakers. Furthermore some words are formed by calquing some indigenous language expressions, e.g. 'to eat money' or 'to eat cash', an expression that is calqued from the Luganda phrase, kulya sente. Such word coinages are meant to fill the 'shortfall' where the English language fails to provide adequate equivalents. Understanding the context of this kind of English usage and the influence from the indigenous languages is helpful in handling inter-cultural discourses, as the same expression may convey different senses to different people in different contexts. So then, this study deals with some peculiarities of Ugandan English, namely; the features of Ugandan English grammar which are influenced by the indigenous languages. Evidence from the Corpus of Ugandan English is explored to establish that indigenous languages in Uganda have a significant influence on the English language variety spoken in the country, and that a large part of English bilingual speakers cannot speak English without transferring the features from their mother tongue or indeed, switching and mixing codes. A British corpus was used for the purposes of comparison with Ugandan English. The research was conducted in Uganda, drawing data from English newspapers, radio and television talk -shows that were recorded to provide a structural analysis of the contact situations. The result of the study points to the fact that, indeed, the phonological, morpho-syntactic and semantic characteristics of Ugandan English have a considerable amount of influence from indigenous local languages. This study is hinged on the assumption that when indigenous languages and the target language come together in a linguistic contact situation, the resulting variety would exhibit distinct phonological, lexical, grammatical and semantic/pragmatic features ( cf. Sankoff, 2001; Thomason, 1995; Thomason & Kaufman, 1988; Winford, 2005). However, some of these innovations have attracted criticism from 'prescriptivists' such as Quirk (1985, 1988, 1990); Gaudio (2011); and Abbot (1991) who perceive them as 'nonstandard', 'incorrect English language usage' and a 'direct translation from the language user's mother tongue into English'. Yet, indigenous languages continue to play important roles in shaping the kind of English language usage in Uganda.
Keywords: Mass media and language -- Uganda; Languages in contact -- Uganda; English language -- Uganda; Language transfer (Language learning) -- Uganda; Communication and culture -- Uganda; Bilingualism -- Uganda; Linguistic demography -- Uganda; Uganda -- Languages